The Causal Relationship Between Blood Lipids and Systemic Lupus Erythematosus Risk: A Bidirectional Two-Sample Mendelian Randomization Study - Wang, Mingzhu; Huang, Shuo; Lin, Xiaoying; Wen, Chengping; He, Zhixing; Huang, Lin (Frontiers in Genetics, 2022)
Background Although observational studies have demonstrated that blood lipids were associated with systemic lupus erythematosus (SLE), the causality of this association remains elusive as traditional observational studies were prone to confounding and reverse causality biases. Here, this study attempted to reveal the potential causal link between SLE and the levels of four blood lipids (HDL cholesterol, LDL cholesterol, TG, and TC). Methods Two-sample Mendelian randomization (MR) was employed to explore the unconfounded causal associations between the four blood lipids and SLE. After a rigorous evaluation of the quality of studies, the single-nucleotide polymorphisms (SNPs) associated with the four blood lipids were selected from the Global Lipids Genetic Consortium (GLGC) consisted of 188577 individuals of European ancestry, and the SNPs related to SLE were selected from a large-scale genome-wide association study (GWAS) database named IEU GWAS. Subsequently, MR analyses were conducted with inverse-variance weighted (IVW), weighted median, weighted mode, simple mode, and MR-Egger regression. Sensitivity analyses were performed to verify whether heterogeneity and pleiotropy led to bias in the MR results. Results Our results demonstrated that a definitively causal association of genetically predicted LDL cholesterol on the risk of SLE (IVW OR: 1.23, 95% CI: 1.02∼1.48, P= 3.37E-02). However, there was no significant causal association between SLE and the other three blood lipids (HDL cholesterol and SLE, IVW OR: 1.20, 95% CI: 0.97∼1.50, P=9.63E-02; TG and SLE, IVW OR: 1.04, 95% CI: 0.71∼1.51, P=8.44E-01; TC and SLE, IVW OR: 1.07, 95% CI: 0.89∼1.29, P = 4.42E-01). Conclusions These data provided evidence indicating LDL cholesterol could show a positive causal effect on SLE in the European population.